Kto to jest geniusz? Kulturowe historie Słowackiego i Mickiewicza po odzyskaniu niepodległości - Kuciński, Paweł (Załącznik Kulturoznawczy, 2019)
In the present article, the author examines the category of the genius on pre-war period’s journalistic material. After regaining independence, the roles of Mickiewicz, Słowacki and the entire group of the Romanticism and its culture was transformed. Conservative criticism, hung between affirmation of Mickiewicz and the tradition of Słowacki, was trying to clarify the phenomenon and the real need of almost mythical forms like genius and national hero in the national culture.